Reaksie op die herontplooiing van Premier Mosiuoa Lekota en die ondemokratiese wyse van aanstelling van Dr. Ivy Matsepe-Casaburri as sy opvolger - Moll, Johan (Faculty of Humanities, University of the Free State, 2013)
In the first part of this article a factual historical analysis is given of the redeployment of the Free State Premier, Patrick Lekota, as a result of the unresolvable faction fights within the ANC, the continuing protest against his transfer and the ongoing “obscurity concerning the objectives of the national leadership” in solving the political debacle. In the second part the background of his successor, Matsepe-Casaburri, is analysed, as well as the undemocratic way in which she was forced into the politics of the Free State, the litigation in respect of Lekota’s removal, the commencement of the Casaburri era and how the serious political fiasco contributed to the consideration of the desirability of the fact that the premiership and leadership of the party should be seated in the same person. The undemocratic conduct of the national leaders of the ANC was a foreshadowing of the increasing trend to subordinate the Constitution and the existing provisions concerning the way in which premiers in the provinces is appointed to what the leaders of the ANC have previously aimed at and decided upon. This article is a critical, historical reconstruction of the role of the national leadership of the ANC and the reaction of the Free State community. The white-centric nature of the reporting, especially of the only newspaper in the Free State which followed the political drama closely and documented it, is supplemented as far as possible by perspectives from other, more liberal, ANC media outside the province who are well-disposed towards the party. If communication is about, among other things, shared meaning by individuals, groups or organisations by openly sharing facts and norms by means of the written and the spoken word, this analysis provides a view on how shared meaning was not reached and optimum communication was by far not pursued or achieved.
Keywords: Mosioua Lekota; Ivy Matsepe-Casaburri; Free State premiership; Undemocratic procedures; National ANC leadership; Constitution